KNEE OSTEOARTHRITIS AND METABOLIC SYNDROME: NEW APPROACHES TO THERAPY - L. I. Alekseeva; E. A. Taskina; N. G. Kashevarova; E. P. Sharapova; S. G. Anikin; E. A. Strebkova; T. А. Korotkova; T. A. Raskina; E. V. Zonova; E. N. Otteva (Научно-практическая ревматология)
Objective: to investigate the effect of diacerein (Diaflex) on some components of metabolic syndrome (MS) in patients with knee osteoarthritis (OA).Subjects and methods. The multicenter open-label prospective study covered 55 patients aged 45 to 74 years with Kellgren–Lawrence Stage II–III knee OA and MS, with a pain intensity of >40 mm on a visual analogue scale, and with a disease duration of 1 to 30 years. The therapy duration was 6 months: Diaflex 50 mg/day for one month, then 50 mg twice daily for 5 months; the patients were followed up for the succeeding 3 months. During each visit, the efficiency and safety of treatment were evaluated; moreover, blood biochemical values were taken into account at the beginning and at the end of therapy.Results and discussion. There was a statistically significant improvement in WOMAC index (all its components and total value) and quality of life using EQ-5D in the first month of therapy and throughout the follow-up. Analysis based on the OMERACT-OARSI criteria indicated high treatment response rates in 92.5% of the patients at the end of therapy and in 92.2% three months after its completion. The body mass index and levels of low-density lipoproteins, triglycerides, glucose, and uric acid significantly decreased during treatment. Adverse events were detected in a small number (5.5%) of cases.Conclusion. Diaflex is an effective and safe drug in the treatment of knee OA in patients with MS. During therapy, there is a rapid and considerable reduction in pain and stiffness and an improvement in the functional state. In addition, the pleiotropic effects of the drug make it possible not only to effectively reduce weight, but also perhaps to improve the course of MS-associated conditions by the observed corrections of metabolic disturbances.